Impact of urban canopy models and external parameters on the modelled urban energy balance in a tropical city. (3rd May 2017) - Demuzere, M.; Harshan, S.; Järvi, L.; Roth, M.; Grimmond, C. S. B.; Masson, V.; Oleson, K. W.; Velasco, E.; Wouters, H.
Abstract : To date, existing urban land surface models (ULSMs) have been mostly evaluated and optimized for mid‐ and high‐latitude cities. For the first time, we provide a comparative evaluation of four ULSMs for a tropical residential neighbourhood in Singapore using directly measured energy balance components. The simulations are performed offline, for an 11 month period, using the bulk scheme TERRA_URB and three models of intermediate complexity (CLM, SURFEX and SUEWS). In addition, information from three different parameter lists are used to quantify the impact (interaction) of (between) external parameter settings and model formulations on the modelled urban energy balance components. Encouragingly, overall results indicate good model performance for most energy balance components and align well with previous findings for midlatitude regions, suggesting the transferability of these models to (sub)tropical regions. Similar to results from midlatitude regions, the outgoing long‐wave radiation and latent heat flux remain the most problematic fluxes. In addition, the various combinations of models and different parameter values suggest that error statistics tend to be dominated more by the choice of the latter than the choice of model. Finally, our intercomparison framework enabled the attribution of common deficiencies in the different model approaches found previously in midlatitude regions: the simple representation of water intercepted by impervious surfaces leading to a positive bias in the latent heat flux directly after a precipitation event; and the positive bias in modelled outgoing long‐wave radiation that is partly due to neglecting the radiative interactions of water vapour between the surface and the tower sensor. These findings suggest that future developments in urban climate research should continue the integration of more physically based processes in urban canopy models, ensure the consistency between the observed and modelled atmospheric properties and focus on the correct representation of urban morphology, water storage and thermal and radiative characteristics. Abstract : Daily temperature (top trace), absolute humidity (middle) and precipitation totals (bottom) for 01 June 2013 to 17 April 2014, observed at Telok Kurau (Singapore). For temperature and humidity, the daily range is indicated by the bars and mean values by the small black symbols.